If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(k + 1) + -1k + -12 = -4(k + 5) + 5 Reorder the terms: -3(1 + k) + -1k + -12 = -4(k + 5) + 5 (1 * -3 + k * -3) + -1k + -12 = -4(k + 5) + 5 (-3 + -3k) + -1k + -12 = -4(k + 5) + 5 Reorder the terms: -3 + -12 + -3k + -1k = -4(k + 5) + 5 Combine like terms: -3 + -12 = -15 -15 + -3k + -1k = -4(k + 5) + 5 Combine like terms: -3k + -1k = -4k -15 + -4k = -4(k + 5) + 5 Reorder the terms: -15 + -4k = -4(5 + k) + 5 -15 + -4k = (5 * -4 + k * -4) + 5 -15 + -4k = (-20 + -4k) + 5 Reorder the terms: -15 + -4k = -20 + 5 + -4k Combine like terms: -20 + 5 = -15 -15 + -4k = -15 + -4k Add '15' to each side of the equation. -15 + 15 + -4k = -15 + 15 + -4k Combine like terms: -15 + 15 = 0 0 + -4k = -15 + 15 + -4k -4k = -15 + 15 + -4k Combine like terms: -15 + 15 = 0 -4k = 0 + -4k -4k = -4k Add '4k' to each side of the equation. -4k + 4k = -4k + 4k Combine like terms: -4k + 4k = 0 0 = -4k + 4k Combine like terms: -4k + 4k = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 9k^2+3=777 | | b(5px-3c)=a(ax-4) | | 2k^2-5=9k | | (2x-y)-(3x+2y)= | | 25b^2+4=5 | | .5c-10=-4 | | (A+B)(A-B)=(A+B)(A+B) | | 5(3x-4)=6x+7 | | 7a-1=5a+11 | | 2x+7=71 | | -3x=-y+1 | | [2(7.7-7)+0.6]= | | n^2=-10n-16 | | 7p+25=4p+28 | | v^2+5v+9v+45= | | 4(3x-1)-(2x-5)+16=2(3x+1)+(2x-5) | | 15y+3=58 | | -9x-10x= | | y-4=-8(x-1) | | 3x^3+27x^2+9x=0 | | 5[10-(3+4)+1]=14 | | 5Xsquared=75 | | -10x+x= | | 9+5x=17+x | | -5x+150=3+0.05x^2 | | 10x^4-12xy-16y^4= | | -5(-2+n)=-35 | | 2x^2-10x+12x^2= | | 4x+3+2x=x-8 | | 2x^4-10x+12x^4= | | 12x^4-12x+12x^4= | | 8m-12=52 |